1995
DOI: 10.1007/bf00552571
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of noise levels in some residential, industrial and commercial areas of Delhi

Abstract: The measurements of noise levels in residential, industrial and commercial areas in the capital city of India, Delhi, were carried out in the month of March and April, 1992. Six sites in residential areas, four in industrial areas and nine in commercial areas were chosen, which were situated in different parts of Delhi. The results of statistical analysis of sound pressure levels show that commercial areas have the highest noise levels followed by industrial and residential areas. Spectral distribution of nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Bhatnagar and Srinivas (1992) in Chandigarh, Pandya and Srivastava (1999) in Jabalpur City, Bhattacharya and De (2000) in Durgapur, Rajamohan (2000) in Madurai and Singh et al (2000) in Dhanbad also observed higher values of noise levels in commercial areas as compared with the values prescribed by Central Pollution Control Board. Dhillon et al (1994) in Ludhiana, Singh and Jain (1995) in Delhi, Joshi (1998) in Indore, Moses et al (2000) in Tamil Nadu, Ravichandran et al (2000) in Pudukkottai and Lalitha et al (2002) in Tiruchirappali and Mishra (2004) C o s m e t i c s h o p i n m a r k e t 5 1 . 30 5 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatnagar and Srinivas (1992) in Chandigarh, Pandya and Srivastava (1999) in Jabalpur City, Bhattacharya and De (2000) in Durgapur, Rajamohan (2000) in Madurai and Singh et al (2000) in Dhanbad also observed higher values of noise levels in commercial areas as compared with the values prescribed by Central Pollution Control Board. Dhillon et al (1994) in Ludhiana, Singh and Jain (1995) in Delhi, Joshi (1998) in Indore, Moses et al (2000) in Tamil Nadu, Ravichandran et al (2000) in Pudukkottai and Lalitha et al (2002) in Tiruchirappali and Mishra (2004) C o s m e t i c s h o p i n m a r k e t 5 1 . 30 5 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This geometric progression wise growth of noise could be mind boggling in view of the everincreasing pace of technological growth. Bhatnagar and Srinivas (1992) in Chandigarh, Dhillon et al (1994) in Ludhiana, Singh and Jain (1995) in Delhi, Ravichandran et al (1997) in Hosur, Joshi (1998) in Indore, Pandya and Shrivastava (1999) in Jabalpur City, Mishra (2004) in Rewa Town, M.P. and Rampal and Rasool (2004) in Jammu City also studied noise levels in various institutional and commercial areas.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et. al report their findings on noise levels of three types of city regions: residential, industrial, and commercial [22]. As social media has been being widely adopted in people's daily lives, social media data becomes an important data source for related research.…”
Section: Urban Region Divergencesmentioning
confidence: 99%
“…Thus, there is a need for contemplation on mitigation of traffic noise by urban planners and road designers before construction of any road network [7]. This inevitable requirement led the need for taking up traffic noise studies by researchers globally including India, especially from the early 1990's, to study the core factors leading to road noise annoyance [8] , [9]. With the incoming of the last decade in India, along with the vital change of demographics in urban areas, vehicles grew at a Compound Annual Growth Rate (CAGR) of 10.5 % between 2002 and 2012 [10].…”
Section: Introductionmentioning
confidence: 99%